A new phytophagous Bracon Fabricius (Hymenoptera, Braconidae) associated with Protium ovatum Engl. (Burseraceae) fruits from Brazilian savannah - Perioto, Nelson Wanderley [UNESP]; Lara, Rogéria Inês Rosa; Ferreira, Cleidson Soares [UNESP]; Fernandes, Daniell Rodrigo Rodrigues [UNESP]; Pedroso, Elizabeth Do Carmo [UNESP]; Volpe, Haroldo Xavier Linhares [UNESP]; Nais, Juliana [UNESP]; Correa, Lilian Roberta Batista [UNESP]; Viel, Silvio Rogério [UNESP] (Magnolia Press, 2011)
Bracon zuleideae Perioto & Lara sp. nov. (Hymenoptera, Braconidae), a new species of phytophagous braconid associated with fruits of Protium ovatum Engl. (Burseraceae) is described and illustrated. Copyright © 2011 · Magnolia Press.
Keywords: Braconinae; Brazil; Neotropical; Phytophagy; Seed predation; Taxonomy